Midrapidity antiproton-to-proton ratio in pp collisons at √s=0.9 and 7 TeV measured by the ALICE experiment - Aamodt, Kenneth; Angelov, Venelin; Busch, Oliver; Glässel, Peter; Grajcarek, Robert; Herrmann, Norbert; Klein, Jochen; Mercado Pérez, Jorge; Oyama, Ken; Pachmayer, Yvonne C.; Schicker, Rainer; Schweda, Kai; et al. (Physical review letters, 2010)
The ratio of the yields of antiprotons to protons in pp collisions has been measured by the ALICE experiment at √s=0.9 and 7 TeV during the initial running periods of the Large Hadron Collider. The measurement covers the transverse momentum interval 0.45<pt<1.05 GeV/c and rapidity |y|<0.5. The ratio is measured to be R|y|<0.5=0.957±0.006(stat)±0.014(syst) at 0.9 TeV and R|y|<0.5=0.991±0.005(stat)±0.014(syst) at 7 TeV and it is independent of both rapidity and transverse momentum. The results are consistent with the conventional model of baryon-number transport and set stringent limits on any additional contributions to baryon-number transfer over very large rapidity intervals in pp collisions.
*ALICE Collaboration: K. Aamodt, V. Angelov, O. Busch, P. Glässel, R. Grajcarek, N. Herrmann, J. Klein, J. Mercado Pérez, K. Oyama, Y. Pachmayer, R. Schicker, K. Schweda, H.K. Soltveit, J. Stachel, S. Vallero, B. Windelband [und 1045 weitere Personen]
Gesehen am 14.11.2022
Im Titel steht der Buchstabe s unter dem Wurzelsymbol